Saving Winslow - Creech, Sharon (Joanna Cotler Books, an imprint of HarperCollinsPublishers, 2018)
When his father brings home an ailing, newborn donkey, Louie names the animal Winslow and takes care of him, but everyone, including Louie's quirky friend Nora, thinks Winslow is not going to survive.